Evaluation of antimicrobial efficacy of Trachyspermum ammi (Ajwain) oil and chlorhexidine against oral bacteria: An in vitro study - Mahesh V Dadpe; Snehal V Dhore; Prasanna T Dahake; Yogesh J Kale; Shrikant B Kendre; Ayesha G Siddiqui (Wolters Kluwer Medknow Publications, 2018)
Introduction: Plaque removal is of utmost importance for control of dental caries and other associated diseases of oral cavity. However, various natural agents have proven their efficacy over chemotherapeutic agents in terms of antibacterial activity against various microorganisms. The effect is mainly due to polyphenol as its major constituent. Aim: In this in vitro study, we aimed to determine the antibacterial efficacy of Trachyspermum ammi oil at different concentrations against five oral bacteria. Hypothesis: Herbal compound, T. ammi oil is effective in reducing five oral plaque-forming bacteria. Materials and Methods: We determined the antimicrobial activity of T. ammi oil (test material) against chlorhexidine (gold standard). Pure cultures of Streptococcus mutans MTCC No 497, Streptococcus oralis MTCC No. 2696, Lactobacillus acidophilus MTCC No. 10307, Lactobacillus fermentum MTCC No. 903, and Candida albicans MTCC No. 183 were obtained and grown in selective culture media. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of both materials were evaluated by serial dilution and disc diffusion method, respectively. Results: Our results revealed that T. ammi oil moderately inhibits bacterial growth with mean MIC of 250, 125, 250, 125, and 250 μg/ml, respectively. Mean MBC for T. ammi oil obtained was 18.60 ± 0.65, 11.60 ± 1.14, 14.10 ± 0.55, 11.50 ± 0.61, and 15.10 ± 0.74 mm. The MIC and MBC values were higher as compared to chlorhexidine gluconate and it was statistically significant. Conclusion: T. ammi (ajwain) can serve as a potential, natural, nontoxic, and economical therapeutic antiplaque agent.